Imprisonment, social policies and intersecting inequalities: (re)producing positions of social exclusion within and beyond prison - Granja, Rafaela Patrícia Gonçalves (2013)
Imprisonment brings together complex effects of a range of intersecting inequalities, which comprise issues of class, ethnicity and gender. Drawing on interviews with twenty male and twenty female prisoners in Portugal, our purpose is to assess, from the prisoners’ point of view, how intersecting inequalities are translated into and shaped by the carceral scenario. Results show that imprisonment co-produces a wide range of complex, and sometimes contradictory, implications within and outside the prison scene. On the one hand, it widens or enables the relationship with the Social State from within prison. On the other hand, imprisonment is inserted in a larger web of societal forces within and beyond prison and establishes itself as an additional mechanism by which inequalities are (re)produced and consolidated. In the face of insufficient public services or social policies aimed to mitigate the social, familial and economic issues emerging during confinement situations, the vulnerabilities co-created by imprisonment are mainly responded to by kinship networks, and in particular by women. However, this caring work is mostly render invisible and under recognized.